2020
DOI: 10.1109/tcomm.2019.2954389
|View full text |Cite
|
Sign up to set email alerts
|

Wake-Up Radio Based Access in 5G Under Delay Constraints: Modeling and Optimization

Abstract: Recently, the concept of wake-up radio based access has been considered as an effective power saving mechanism for 5G mobile devices. In this article, the average power consumption of a wake-up radio enabled mobile device is analyzed and modeled by using a semi-Markov process. Building on this, a delay-constrained optimization problem is then formulated, to maximize the device energy-efficiency under given latency requirements, allowing the optimal parameters of the wake-up scheme to be obtained in closed form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…We also showed that the impact of such negligible errors is very low on power consumption and buffering delay. Furthermore, in our previous work [23], [24], we introduced an offline method to optimize the WuS configuration (i.e., the wake-up cycle period) based on a delay bound under the assumption of Poisson traffic. In cases where traffic dynamics vary over time, the WuS optimization method in [23], [24] requires reconfiguration of the WuS parameters, which need to be communicated to the mobile device, and thus increases the control signaling overhead as well as the associated energy consumption.…”
Section: A Wake-up Based Access and State-of-the-artmentioning
confidence: 99%
See 1 more Smart Citation
“…We also showed that the impact of such negligible errors is very low on power consumption and buffering delay. Furthermore, in our previous work [23], [24], we introduced an offline method to optimize the WuS configuration (i.e., the wake-up cycle period) based on a delay bound under the assumption of Poisson traffic. In cases where traffic dynamics vary over time, the WuS optimization method in [23], [24] requires reconfiguration of the WuS parameters, which need to be communicated to the mobile device, and thus increases the control signaling overhead as well as the associated energy consumption.…”
Section: A Wake-up Based Access and State-of-the-artmentioning
confidence: 99%
“…To the best of our knowledge, this is the first attempt to introduce online wake-up scheduling decisions with traffic prediction capabilities into the wake-up scheme. Unlike previous works [5], [23], [24], the WuSched-Online is not tied to any specific traffic models and operates dynamically. inter-arrival times of n th and n+1 th packets at gNB An packet arrival times of n th packets at gNB Dn n th packet's buffering delaȳ Dn estimated delays of n th packet (buffered or forecast) Wn time duration between decoding n th and n+1 th packets by UE Hn…”
Section: B Contributions and Noveltymentioning
confidence: 99%
“…1). However, if the WuS configuration (namely, t w and t i ) is not properly optimized for the upcoming traffic, the immediate waking up of the UE can either adversely increase its energy consumption and eventually decrease the benefits of using WuS (meaning that the UE can tolerate longer w-cycles) or even create a worst case scenario, in which the UE may not even satisfy its delay requirements (implying the need for shorter w-cycles) [8].…”
Section: A Review Of Wake-up Schemementioning
confidence: 99%
“…As soon as a packet arrive at the transmission buffer of the base station, the wake-up indicator is assumed to be sent at the next upcoming wake-up instant. In our previous work [7], [8], we introduced an off-line method to optimize the WuS configuration (i.e., the wake-up cycle period) based on a delay bound under the assumption of Poisson traffic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation